Initial validation of the coach-created Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ-C). (January 2016) - Appleton, Paul R.; Ntoumanis, Nikos; Quested, Eleanor; Viladrich, Carme; Duda, Joan L.
Abstract: This article employs Duda's (2013) hierarchical conceptualization of the coach-created motivational climate to inform the validation of a questionnaire (Empowering and Disempowering Motivational Climate Questionnaire-Coach; EDMCQ-C) that assesses junior athletes' perceptions of the social environmental dimensions proposed by achievement goal theory and self-determination theory. Confirmatory factor analyses (CFA) were initially employed to reduce the number of items required to measure the targeted climate dimensions. A series of competing models were then tested to determine the best representation of the questionnaire's factor structure. The findings revealed that exploratory structural equation modelling (ESEM) provided a better fit of the data to the hypothesised model than CFA solutions. Specifically, the bi-factor ESEM provided the best fit, although parameter estimates suggest that none of the ESEM solutions replicated the underlying theoretical model of the motivational climate proposed by Duda (2013). The evidence from this study suggests that the EDMCQ-C is a promising, parsimonious questionnaire to assess empowering and disempowering facets of the motivational climate albeit the development of the questionnaire remains a work in progress. Highlights: Number of items needed to measure empowering and disempowering climates reduced to 34. ESEM solutions provide better fit to the data compared to CFA models. Bi-factor ESEM solution provides best fit to the data. Current study provides platform to further establish the psychometrics of the EDMCQ-C.